Onset polarity in bipolar disorder : differences in clinical features and course of illness - Sólveig Birna Júlíusdóttir 1990- (2022)
Studies have suggested that certain clinical factors and the future course of bipolar disorder can, in part, be predicted by the polarity of the first major episode experienced. Furthermore, growing evidence supports the idea that most individuals with bipolar disorder experience a depressive first-onset. The present study researched what characterizes individuals receiving care at the only specialized bipolar clinic in Iceland and compared specific clinical characteristics based on onset polarity. Information was issued from patients' medical records attending the bipolar outpatient clinic (N = 66) at Landspítali, The National University Hospital of Iceland. Results showed that the mean onset age was relatively higher than in previous studies, just over 29 years. Individuals had been hospitalized on average 2.4 times and been ill for 4.8 years on average. A majority, or 53%, had a manic/hypomanic onset, whereas 16.7% experienced a depressive onset, 10.6% a psychotic onset, and 12.1% an unspecified bipolar disorder onset. No significant difference was found in clinical factors between the four onset groups. In addition, no significant association was found between onset polarity and hospitalizations or the number of manic or depressive episodes. Results gave a clearer picture of patients attending the bipolar clinic and may therefore benefit clinicians. The results can also lead the way for future research on the topic. Future research might, for example, focus on enlarging the group of participants and look into clinical factors like suicidal inclinations and more detailed demographic factors, such as work status and education. Keywords: Bipolar disorder, onset polarity, first episode polarity, depression, mania, bipolar clinic.